Antimicrobial properties and the influence of temperature on secondary metabolite production in cold environment soil fungi - Yogabaanu, U.; Weber, J.F.F.; Convey, P.; Rizman-Idid, M.; Alias, S.A. (Elsevier, 2017)
The Arctic and Antarctic share environmental extremes. To survive in such environments, microbes such as soil fungi need to compete with or protect themselves effectively from other soil microbiota and to obtain the often scarce nutrients available, and many use secondary metabolites to facilitate this. We therefore (i) screened for antimicrobial properties of cold-environment Arctic and Antarctic soil fungi, and (ii) identified changes in the secreted secondary metabolite profiles of a subset of these strains in response to temperature variation. A total of 40 polar soil fungal strains from King George Island, maritime Antarctic and Hornsund, Svalbard, High Arctic, were obtained from the Malaysian National Antarctic Research Centre culture collections. The plug assay technique was used to screen for antimicrobial potential against Gram-positive and Gram-negative human pathogenic bacteria (Bacillus subtilis, B. cereus, Pseudomonas aeruginosa, Enterococcus faecalis and Escherichia coli). About 45% of the tested fungal strains showed antimicrobial activity against at least one tested microorganism. Three fungal isolates showed good bioactivity and were subjected to secondary metabolite profiling at different temperatures (4, 10, 15 and 28 °C). We observed a range of responses in fungal metabolite production when incubated at varying temperatures, confirming an influence of environmental conditions such as temperature on the production of secondary metabolites.